Antifungal Lotion as Value-Added Product for Harvested BSFL Processing: Simple Process Design and Economic Evaluation - Nugroho, Daniel Setiyo; Yu Shen, Cheng; Han Chou, Tzung; Hartini, Nina; Ya Chiu, Hsiang (Jurnal Bahan Alam Terbarukan, 2019)
Advancing the value of products derived from insect biomass is a potential way to increase the demand of processing insect as renewable and sustainable resources. Among several species of insect, black soldier fly larvae (Hermetia illucens) is promising biomass source because of its favorable characteristics such as easy cultivation, fast-growing, and worldwide distribution. One problem that could limit the development of insect-based bioproduct is the low market price and displeasing uses for edible food. To overcome this problem, value-added product development is necessary to carried out. Thus, establish an antifungal lotion using extracted materials from BSFL biomass was discussed in this report followed by the economic evaluation and sensitivity analysis. The result reveal that equipment availability in market and raw material readiness espouse the production expediency. From the economic aspect, the direct fixed capital cost (DFC) for a plant of this capacity is around US$3.6 million, or approximately 6 times the total equipment cost. Thus, the net profitability will remain stable even the market price of BSFL might fluctuate in the range of 20%. In contrary, the change in main product price was impactful to the rate of return (ROI), internal rate of return (IRR) and, payback time (PBT) value. The overall result suggests that this project is worthy to being built.